2020
DOI: 10.1155/2020/8959210
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Core Prognosis-Related Candidate Genes in Cervical Cancer via Integrated Bioinformatical Analysis

Abstract: Purposes. Cervical cancer (CC) is one of the highest frequently occurred malignant gynecological tumors with high rates of morbidity and mortality. Here, we aimed to identify significant genes associated with poor outcome. Materials and methods. Differentially expressed genes (DEGs) between CC tissues and normal cervical tissues were picked out by GEO2R tool and Venn diagram software. Database for Annotation, Visualization and Integrated Discovery (DAVID) was performed to analyze gene ontology (GO) and Kyoto E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
(23 reference statements)
1
14
0
Order By: Relevance
“…Although the timing of sleep deprivation was different for the microarray experiments with sleep deprivation performed for five hours starting between ZT 4 and ZT 6, the microarray data set was verified, in part by Vescey and colleagues through qPCR following experiments in which sleep deprivation was performed from ZT 0 to ZT 5 [ 10 ]. We analyzed the microarray data set from GEO using the available GEO2R function as has been done in other recently published studies [ 51 , 52 ] to find differentially expressed genes and genes not affected by sleep deprivation. Surprisingly, we found only 49 genes that were differentially expressed after sleep deprivation in common between the two data sets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the timing of sleep deprivation was different for the microarray experiments with sleep deprivation performed for five hours starting between ZT 4 and ZT 6, the microarray data set was verified, in part by Vescey and colleagues through qPCR following experiments in which sleep deprivation was performed from ZT 0 to ZT 5 [ 10 ]. We analyzed the microarray data set from GEO using the available GEO2R function as has been done in other recently published studies [ 51 , 52 ] to find differentially expressed genes and genes not affected by sleep deprivation. Surprisingly, we found only 49 genes that were differentially expressed after sleep deprivation in common between the two data sets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therapeutic targeting of these repair constituents may be uniquely advantageous in CC, particularly to be most effective in combination with standard therapy. For example, it has been reported that overexpression of AURKB is correlated with poor clinical prognosis in CC patients, suggesting its interference with a vital function, and thus serving as a potential therapeutic target [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To validate the expression of the key DEGs, the Gene Expression Profiling Interactive Analysis (GEPIA) website ( http://gepia2.cancer-pku.cn/#index ) was applied to analyze the data of RNA sequencing expression based on thousands of samples from the GTEx projects and TCGA [ 23 ]. The association between overall survival (OS) and the genes expressed in GC patients was determined using GEPIA.…”
Section: Methodsmentioning
confidence: 99%